Flash Nanoprecipitation for Co-Delivery of Diagnostic Magnetic Nanoparticles and Anti-Inflammatory Drugs in Polymeric Nanocarriers - Pohlit, Hannah; Weber, Alex Eric; Ansari, Shaquib Rahman; Suarez-Lopez, Yael; Chen, Qianying; Paraskeva, Christina; Koliaraki, Vasiliki; Teleki, Alexandra (Uppsala University, 2026)
Chronic inflammatory diseases may benefit from nanocarrier platforms that co-deliver hydrophobic anti-inflammatory drugs and imaging agents. Here, we report polymeric theranostic nanocarrier dispersions produced by flash nanoprecipitation (FNP) that encapsulate flame-made manganese-doped superparamagnetic iron oxide nanoparticles (SPIONs; Mn0.25Fe2.75O4) together with T‑5224, a model small-molecule inhibitor of the c‑Fos/c‑Jun activator protein‑1 (AP‑1) complex. We first mapped key formulation and process parameters governing dispersion properties, including PLA–PEG molecular weight, total solute concentration, solvent-to-antisolvent ratio, and SPION:polymer mass ratio. These studies identified conditions yielding smaller, narrowly distributed dispersions. Using the optimized formulation, T‑5224/SPION nanocarrier dispersions were purified by magnetic separation and exhibited hydrodynamic diameters
Keywords: Pharmaceutical sciences; Nanomaterials; Medical and Health Sciences; Medicin och hälsovetenskap; Nanotechnology for Materials Science; Nanoteknisk materialvetenskap; Pharmaceutical Sciences; Farmaceutiska vetenskaper